Comfortably numb: Ecotoxicity of the non-steroidal anti-inflammatory drug ibuprofen on Phaeodactylum tricornutum - Feijão, Eduardo (2021)
Emerging pollutants such as pharmaceuticals are continuously released to aquatic environments posing a rising threat to marine ecosystems. Yet, monitoring routines and ecotoxicity data on biota worldwide for these substances are lacking. Non-steroidal anti-inflammatory drugs are among the most prescribed and found pharmaceuticals in aquatic environments. The toxicity effects of environmentally relevant concentrations of ibuprofen on primary productivity, oxidative stress and lipid metabolism of the diatom Phaeodactylum tricornutum were assessed. Diatom cultures were exposed to 0, 0.8, 3, 40, 100 and 300 μg L-1 ibuprofen concentrations, usually found in the vicinity of wastewater treatment plants and coastal environments. Higher concentrations (100 and 300 μg L-1) had a negative impact in P. triconutum growth, inhibiting the chloroplastic energy transduction in the electron transport chain resulting in lower energy reaching the PS I (r2 = - 0.55, p < 0.05). In contrast, the mitochondrial electron transport and available energy increased (r2 = 0.68 and r2 = 0.85, p < 0.05 respectively), mostly due to enhancements in lipid and protein contents as opposed to reduction of carbohydrates. A general up-regulation of the antioxidant enzymes could contributed to alleviate oxidative stress resulting in the decrease of lipid peroxidation products (r2 = 0.77, p < 0.05). Canonical analysis of principal components was performed and successfully discriminated exposure groups, with optical data excelling in classifying samples to different ibuprofen concentrations, being potentially used as environmental indicators. Finally, the identified mild to severe effects of ibuprofen on diatoms are likely to be exacerbated by the sustained use of this drug worldwide, underpinning the urgency of evaluating the impacts of this pharmaceutical on coastal and marine trophic webs.